Reversible conversion-alloying of cobalt-bismuth oxide nanoneedles for long-life lithium storage anodes - Devina, Winda; Sarofil, Anith Dzhanxinah Mohd; Chandra, Christian; Park, Hyeon Seo; Park, Jae -Ho; Chung, Kyung Yoon; Chang, Wonyoung; Kim, Jaehoon (Elsevier BV, 2023)
Materials that undergo combined conversion and alloying reactions are promising as anodes for lithium storage application because they can accommodate multiple lithium ions. However, irreversible conversion reactions, large voltage hysteresis, poor rate capabilities, and low initial Coulombic efficiencies during continuous discharge-charge cycling make practical applications of conversion-alloying materials challenging. Herein, we present cobalt-bismuth oxide (CBO) nanoneedles, a new bimetallic material in which Li+-ion uptake proceeds stepwise, thus effectively suppressing volume expansion. During the initial lithiation stage, the CBO nanoneedles undergo a conversion reaction to form nanodomains of low-oxidation-state Co delta+ ( delta <= 2) in a Li2O matrix. At the next potential platform, the Bi phase attracts Li+ ions via an alloying reaction, while the Co delta+/Li2O phase hinders excessive volume expansion. Consequently, the CBO electrode delivers a high reversible discharge capacity of 392 mAh g(-1) at 50 mA g(-1) for up to 100 cycles. Further, an ultrastable long-term capacity of 300 mAh g(-1) at 250 mA g(-1) is realized over 1000 cycles. The stepwise lithiation process decreases volume expansion significantly (by similar to 10%), which leads to good cyclability. Owing to their ease of preparation and excellent performance characteristics, CBO nanoneedles are an attractive long-life anode material for lithium-ion batteries.